Involvement in Subject Teachers Association (MGMP), Pedagogical and Professional Competencies of Civic Teachers, And Learning Outcomes: A Correlational Study - Safitri, Auliah; Gafur, Abdul (Universitas Negeri Malang, 2019)
This study aims to determine the relationship of teacher involvement in the Subject Teachers Association (MGMP), pedagogical and professional competencies of civic teachers with the learning outcomes of high school students in Malang. Data were analyzed descriptively using a correlational design. Hypothesis testing was done by analyzing the parametric correlation between the independent variables and the dependent variable partially. The results of this study indicate that there is a positive and significant relationship between involvement in MGMP, pedagogical competence, and professional competence of civic teachers and the learning outcomes of high school students in Malang. All hypotheses show a significant relationship.